Study on low temperature plasma combined with AC/Mn + TiO2–Al2O3 catalytic treatment of sewage-containing polyacrylamide. (9th February 2023) - Wang, Xiaobing; Guan, Fengwei; Huang, Zhigang; He, Hao; Wang, Lu; Li, Kaifeng
Abstract: With the introduction of tertiary oil recovery technology, polymer oil drive technology has effectively improved the recovery rate of crude oil, but the resulting oilfield wastewater-containing polyacrylamide (PAM) is viscous and complex in composition, which brings difficulties to wastewater treatment. The treatment of this kind of wastewater has become an urgent problem to be solved, and the removal of PAM is the key. In this paper, a dielectric barrier discharge (DBD) co-catalyst was used to treat PAM-containing solutions to investigate the effect of different catalytic reaction systems on the degradation of PAM. The morphological changes of the PAM solution before and after the reaction were also studied by the environmental electron microscope scanner (ESEM), and the information of the functional groups in the solution before and after the reaction was studied by infrared spectroscopy analysis of the PAM solution. The degradation rate rose by 26.3% in comparison to that without discharge when AC/Mn + TiO2 and Al2 O3 were combined and catalyzed at a mass ratio of 2:1 and a discharge period of 300 min. The degradation rate rose by 19.3 and 6.8%, respectively, in comparison to AC/Mn + TiO2 and Al2 O3 -catalyzed alone. It demonstrates that this catalytic system has the optimum catalytic effect. HIGHLIGHT: In this paper, the feasibility of low-temperature plasma generated by dielectric barrier discharge (DBD) to degrade poly-containing wastewater was studied. From the perspective of improving the degradation efficiency, a double glass DBD reactor with a water-cooling function was designed, and the effect of low-temperature plasma on the degradation rate of PAM solution under different catalyst combinations conditions was studied. Graphical Abstract